Teach your children well - Macnab, Andrew John (GHMJ (Global Health Management Journal), 2019)
This perspective looks at the importance of providing parents with the information they need to make informed decisions about their children’s health, and particularly of encouraging parents to teach their children health-related practices that help prevent illness and injury; it is the viewpoint of a grandparent who is also a children’s doctor.